2005
DOI: 10.1186/bcr1296
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible factor 1 alpha and its downstream targets in fibroepithelial tumors of the breast

Abstract: Introduction Hypoxia-inducible factor 1 (HIF-1) alpha and its downstream targets carbonic anhydrase IX (CAIX) and vascular endothelial growth factor (VEGF) are key factors in the survival of proliferating tumor cells in a hypoxic microenvironment. We studied the expression and prognostic relevance of HIF-1α and its downstream targets in phyllodes tumors and fibroadenomas of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
3
15
0
3
Order By: Relevance
“…These markers include ATG16L1 and the cathepsins (K and D) for autophagy, as well as carbonic anhydrase IX (CAIX) and HIF1-a for oxidative stress. [49][50][51][52][53][54][55][56] Furthermore, re-analysis of the published transcriptional profiles 15 of laser-captured tumor stroma, isolated from human breast cancers, reveals strong evidence for the enrichment of autophagy genes, lysosomal markers, as well as indicators of oxidative stress (such as peroxisomes), which were associated with tumor recurrence and metastasis. 16,30 These tumor stroma transcriptional profiles also showed significant overlap with the transcriptional profiles of Cav-1 (-/-) null stromal cells, 16,30,31 and Alzheimer disease brain (known to be associated with oxidative stress).…”
Section: Methodsmentioning
confidence: 99%
“…These markers include ATG16L1 and the cathepsins (K and D) for autophagy, as well as carbonic anhydrase IX (CAIX) and HIF1-a for oxidative stress. [49][50][51][52][53][54][55][56] Furthermore, re-analysis of the published transcriptional profiles 15 of laser-captured tumor stroma, isolated from human breast cancers, reveals strong evidence for the enrichment of autophagy genes, lysosomal markers, as well as indicators of oxidative stress (such as peroxisomes), which were associated with tumor recurrence and metastasis. 16,30 These tumor stroma transcriptional profiles also showed significant overlap with the transcriptional profiles of Cav-1 (-/-) null stromal cells, 16,30,31 and Alzheimer disease brain (known to be associated with oxidative stress).…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy induction in cancer cells may occur due to hypoxia (13,32), and it has been previously demonstrated that expression of hypoxiainducible factor 1α (HIF-1α) downstream targets is associated with a higher histologic grade in fibroepithelial tumors of the breast (33). In this scenario autophagy provides the nutrients needed for cancer survival and stabilization of HIF-1α allows for instance that higher grade phyllode tumors adapt to hypoxia (30).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated epidermal growth factor receptor (EGFR) overexpression in phyllodes tumors, with increasing expression accompanying increasing degree of malignancy [14,15]. Increased expression of stromal HIF-1 alpha [16], c-myc [11], CD10 [17], nitric-oxide synthase [18], heparan sulfate expression [19], Ki-67 [20], increased microvessel density, and VEGF [21,22] with increasing degree of malignancy have also been shown. Increased cell cycle deregulation has been observed with higher tumor grade [23].…”
Section: Introductionmentioning
confidence: 97%